Role of interferon regulatory factor 1 in governing Treg depletion, Th1 polarization, inflammasome activation and antitumor efficacy of cyclophosphamide. Issue 5 (16th October 2017) - Buccione, Carla; Fragale, Alessandra; Polverino, Federica; Ziccheddu, Giovanna; Aricò, Eleonora; Belardelli, Filippo; Proietti, Enrico; Battistini, Angela; Moschella, Federica
Abstract : The antitumor effectiveness of cyclophosphamide (CTX) and other chemotherapeutics was shown to rely not only on direct cytotoxicity but also on immunogenic tumor cell death and systemic immunomodulatory mechanisms, including regulatory T cell (Treg) depletion, Th1 cell polarization, type I interferon (IFN) and proinflammatory cytokine production. IFN regulatory factor (IRF)‐1 is a transcriptional regulator of IFNs and IFN‐inducible genes, involved in the control of Th1 and Treg differentiation and in sterile inflammation. Aim of this study was to explore the role of IRF‐1 in CTX‐induced antitumor effects and related immune activities. This study shows for the first time that IRF‐1 is important for the antitumor efficacy of CTX in mice. Moreover, experiments in tumor‐bearing C57BL/6 mice showed that Irf1 gene expression in the spleen was transiently increased following CTX administration and correlated with the induction of Th1 cell expansion and of Il12p40 gene expression, which is the main Th1‐driving cytokine. At the same time, CTX administration reduced both Foxp3 expression and Treg cell percentages. These effects were abrogated in Irf1 −/− mice. Further experiments showed that the gene and/or protein expression of caspase‐1, iNOS, IL‐1β, IL‐6 and CXCL10 and the levels of nitric oxide were modulated following CTX in an IRF‐1‐direct‐ or ‐indirect‐dependent manner, and highlighted the importance of caspase‐1 in driving the sterile inflammatory response to CTX. Our data identify IRF‐1 as important for the antitumor efficacy of CTX and for the regulation of many immunomodulatory activities of CTX, such as Th1 polarization, Treg depletion and inflammation. Abstract : What's new? Chemotherapy drugs such as cyclophosphamide (CTX) affect the expression of hundreds of genes; however, the molecular mechanisms that regulate these pleiotropic effects are not well understood. In this study, the authors found that interferon regulatory factor (IRF)‐1 plays a crucial role in governing the antitumor activity of CTX, via immunomodulatory activities such as depletion of Tregs, Th1 cell polarization, and proinflammatory cytokine production, and via apoptotic pathways. IRF‐1 may thus serve as a useful predictive biomarker of response to CTX in cancer patients.